Exploring the Qur'anic Literacy Tradition: A Review of Traditional and Modern Pesantren in Tuban Indonesia - Muhammad Jamil (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
The Qur'anic literacy in pesantren plays a crucial role in eliminating Qur'anic illiteracy and fostering a generation of literate individuals. This article aimed to explore the tradition of Qur'anic literacy and its significance in both traditional and modern pesantren in Tuban. The research methodology was qualitative, employing a field study with a phenomenological approach to comprehend the tradition of Qur'anic literacy and its interpretation. Data was gathered through interviews, observations, and documentation, and was analyzed using an interactive analysis model consisting of data reduction, data presentation, and conclusion drawing. The analysis is based on Karl Mannheim's theory of the sociology of knowledge, which posits that actions and interpretations of meaning influence human behavior. Mannheim identifies three types of meaning in social action: objective, expressive, and documentary. The study concludes that the tradition of reading and writing the Qur'an in traditional and modern pesantren involves complex interpretations. The objective meaning is derived from social and religious norms in Islamic boarding schools, making this tradition an integral part of religious education and identity. The expressive meaning for kiai and santri represents obedience, devotion, and spiritual relationships influenced by personal backgrounds and relationships with teachers. The documentary meaning reflects the cultural aspects of pesantren, influences the actions and values of the community, and mirrors the ideology of traditionalism, adaptability, and respect for religious authority. Despite differences in educational approaches, these traditional and modern pesantren share similarities in scientific lineage ‘sanad’, which makes the roots of tradition and interpretation similar. This study underscores the importance of understanding the dynamics of tradition in pesantren.